2004
DOI: 10.1103/physrevb.70.115419
|View full text |Cite
|
Sign up to set email alerts
|

Image-potential states of single- and multiwalled carbon nanotubes

Abstract: The existence of low angular momentum image-potential states is predicted both for single-and multiwalled nanotubes. The states are confined between the self-induced potential on the vacuum side and the surface barrier, created by the central ascent in the transverse nanotube potential. Effective interactions near the surface of the nanotube are modeled with a cylindrical jelliumlike surface barrier, parameterized to ensure the correct transition into the long-range image potential. Binding energies and wave f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
6
15
0
Order By: Relevance
“…When graphene layers are assembled into a graphite crystal, the interlayer band can be viewed as a consequence of trapping and hybridization of the lowest-energy 1 + image-potential state. Moreover, the unoccupied electronic states in other carbon-based nanostructures, like fullerenes, 15 fullerites, 14 and nanotubes [34][35][36] can be understood as having the common origin with the graphene image-potential states found in the present work. A large extent of wave functions of the imagepotential states in the vacuum implies that they are very sensitive to any change of shape or/and environment of the graphene sheet.…”
supporting
confidence: 55%
“…When graphene layers are assembled into a graphite crystal, the interlayer band can be viewed as a consequence of trapping and hybridization of the lowest-energy 1 + image-potential state. Moreover, the unoccupied electronic states in other carbon-based nanostructures, like fullerenes, 15 fullerites, 14 and nanotubes [34][35][36] can be understood as having the common origin with the graphene image-potential states found in the present work. A large extent of wave functions of the imagepotential states in the vacuum implies that they are very sensitive to any change of shape or/and environment of the graphene sheet.…”
supporting
confidence: 55%
“…For a strong centrifugal repulsion associated with high values of electron angular momenta, single wall carbon nanotubes (SWNT) were predicted to support the tubular image states that form in the potential well between the repulsive barrier and the long-range image-interaction [16]. On the other hand, our recent study [17] has suggested that in addition to tubular image states, both single and multiwalled carbon nanotubes can support low-and zero-angular momentum image states with weak transverse penetrations into the bulk (see Fig. 1).…”
mentioning
confidence: 91%
“…More exotic IPSs appear on curved graphene, typical examples of which are tubular IPSs extended around carbon nanotubes [5] and superatom molecular orbitals of C 60 fullerene [6]. The hybridization of these IPSs results in the interlayer states with a nearly-free-electron feature in a variety of graphitic materials such as graphite [3], multiwalled [7,8] or bundles [9,10] of carbon nanotubes, fullerite solids [11,12], and carbon nanopeapods [13]. In particular, the interlayer states in graphite are believed to be crucial for the superconductivity of graphiteintercalation compounds [14].…”
mentioning
confidence: 99%